Solutions to improve quality sustainable poverty reduction in Phu Tan district, Ca Mau province - Phạm, Thị Tám (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
Sustainable poverty reduction is a complex issue and requires a long-term implementation strategy. In the past time, the organization and implementation of poverty reduction policies in Phu Tan district, Ca Mau province have obtained certain results, people’s lives have changed markedly; This shows the great efforts and determination of the Party Committee, authorities and people of Phu Tan district in the implementation of poverty reduction policies. However, the poverty reduction in the following years, besides the advantages, will still have many difficulties and challenges. So, how to effectively implement sustainable poverty reduction is an issue that leaders and state agencies are very interested in. This study aims to propose solutions to improve the quality of sustainable poverty reduction in Phu Tan district, Ca Mau province in the coming time.